Performance Evaluation of Channel Estimation in OFDM System for Different QAM and PSK Modulations - Surinder Singh; Hari Ram; Sandeep Singh Gill (International Journal of Electrical and Computer Engineering (IJECE), 2011)
To recover accurate transmitted data at the receiver end, the information regarding channel state derived from channel estimation methods play a very important role in any communication system. In this paper the performance evaluation of different types of QAM and PSK modulations with three different channel estimation methods in OFDM system for wireless communication in frequency domain for slow fading channel is compared. The results must be useful in OFDM based applications like IEEE 802.16(d) and equivalent standards.DOI:http://dx.doi.org/10.11591/ijece.v1i2.148